ANALYSIS OF FACTORS AFFECTING DIVIDEND POLICY MODERATING VARIABLES USING AS GROWTH IN BANKING COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE 2012-2018 - Adibra, Muhammad Zulfikar (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aimed to get empirical evidence on disclosure of cash ratio, debt to equity ratio, return on assets and operating cash flow effect on dividend policy with growth as moderating variable in the annual report on banking companies listed in Indonesia Stock Exchange period 2012 to 2018. This research was conducted at the Indonesian Stock Exchange (BEI) Of the entire banking firms from 2012 to 2018. The sample in this study were selected by purposive sampling method. The data analysis was conducted on the descriptive statistical factor analysis, and regression analysis. Factor analysis using confirmatory factor analysis. Hypothesis testing using bivariate correlation analysis with Regresion Moderated Analysis (MRA) with SPSS (Statistical Package For Social Science) version 17.0. The results of this study indicate that partial cash ratio had no effect and no significant effect on dividend policy, debt to equity ratio influential and significant to dividend policy, return on assets has no effect and no significant effect on dividend policy, operational cash flow effect and significant to dividend policy , simultaneous cash ratio, debt to equity ratio, return on assets and operating cash flow effect and significant to dividend policy and growth as moderating variable able to moderate the relationship between the cash ratio, debt to equity ratio, return on assets and operating cash flow against policy dividend.